A parametric study on the droplet detachment process from the ceiling under the effect of gravity. Issue 2 (14th December 2018) - Manik, Jai; Dalal, Amaresh; Natarajan, Ganesh
Abstract : Purpose: The purpose of this paper is to numerically investigate the effect of various parameters such as density ratio, surface wettabilities and Weber number on the droplet dripping and detachment process. Design/methodology/approach: By using algebraic volume of fluid method, the governing equations are solved using a collocated finite volume approach in two-dimensions. Findings: The results indicate that, for small densities of droplet, it adheres to the surface except when the surface is hydrophobic, while an increase in Weber number or presence of an additional droplet in the vicinity led to detachment. Originality/value: The paper explores various characteristics of a droplet when two competing forces, namely, gravity and surface tension, act simultaneously. The detachment is observed for a given initial droplet size, as it becomes denser in an uniform gravitational field. The effect of droplet affinity for two droplets is also presented using the simulations.